Analisis Pengendalian Limbah Kantong Semen (Reject) Menjadi Kantong Kemasan Suvenir dengan Teknik Ecoprint (Studi Kasus : PT. Solusi Bangun Indonesia Tbk) - Andika Prastya; Oto Prasadi; Taufan Ratri Harjanto; Saipul Bahri (Jurnal Pengendalian Pencemaran Lingkungan (JPPL), 2022)
The company's need for cement bag raw materials is getting higher, so that the use of paper will be greater and efforts to bring raw materials to the factory will increase, the potential for energy use is higher and the emergence of paper waste will also be higher. This study aims to analyze the control of cement bag waste (reject) into suvenir packaging bags with ecoprint techniques at PT. Solusi Bangun Indonesia Tbk Cilacap Factory. The data used is actual data in the field taken in january – august 2021 and 2022. The method used is comparative descriptive by comparing cement bags damaged by the production bag process into suvenir bags for 2 years. The implementation process of utilizing cement bag waste to the community is carried out using the ecoprint technique because it is an environmentally friendly technique. Based on the results obtained, the total number of cement bags produced in 2021 is more than in 2022 while cement bags damaged due to the production bag process that failed production or reject in 2021 have a very large number of the 4 types of raw materials used with a total damage of 58,534 pcs for 2021 and 17,235 pcs for 2022. The implementation that has been implemented in the use of broken cement bags into suvenir bags has been carried out in 3 villages, namely Kebonmanis Village, Tegalreja Village and Gunung Simping Village.